Gravitational Collapse of Solar Nebulae and the Processes of Star Formation - Belay Sitotaw Goshu (Britain International of Exact Sciences (BIoEx) Journal, 2024)
The creation of stars and planetary systems depends on the gravitational collapse of solar nebulae. Comprehending the variables that impact this collapse, such as changes in temperature and density within molecular clouds, is essential to understanding the initial phases of star formation. This work aims to apply numerical simulations and theoretical models to examine the relationship between Jean's mass temperature and density variations in a solar nebula. The Jeans mass was determined in this study by running several simulations at various densities (10−20 kg/m³ to 10−15 kg/m³) and temperatures (10 K to 100 K). The conditions required for gravitational instability were visualized by modeling the gravitational potential, density, velocity, and magnetic field. Based on the data, it can be observed that the Jeans mass increases dramatically from 10 K to 100 K, reaching magnitudes of about 1.272×1033 kg at a density of 10−20 kg/m³. In addition, changes in density between 10−20 and 10−18 kg/m³ result in significant fluctuations in Jean's mass, especially between 20 and 100 K in temperature. The results demonstrate how important temperature and density are in a molecular cloud's ability to remain stable in space. While the threshold mass for instability is lowered at higher densities, collapse at higher temperatures requires bigger masses. These findings provide important new information about the mechanisms behind star formation and are consistent with theoretical forecasts and observational facts. Future research on more intricate physical processes, like radiative transmission and magnetic field dynamics, is advised to improve our comprehension of how stars emerge in molecular clouds.